2022
DOI: 10.1155/2022/6018037
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-17-5p Protects against Propofol Anesthesia-Induced Neurotoxicity and Autophagy Impairment via Targeting BCL2L11

Abstract: Background. Propofol (PPF) has been shown in studies to cause cognitive impairment and neuronal cell death in developing animals. PPF has been demonstrated to decrease the expression of microRNA-17-5p (miR-17-5p) in a recent study. Nonetheless, the function of miR-17-5p in PPF-induced neurotoxicity and related mechanisms is uncharacterized. Methods. After the induction of neurotoxicity by treating the SH-SY5Y cells with PPF, qRT-PCR was conducted to evaluate the level of miR-17-5p. Using MTT and flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…41 microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been found to be involved in the neurotoxicity process of propofol. 42,43 MicroRNAs (miRNAs) are endogenous noncoding RNA molecules with a length of approximately 22 nucleotides that regulate cellular processes by inhibiting the translation of messenger RNAs. 44 MiRNAs have become a research hotspot on the neurotoxicity of anesthetics in recent years.…”
Section: Noncoding Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…41 microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been found to be involved in the neurotoxicity process of propofol. 42,43 MicroRNAs (miRNAs) are endogenous noncoding RNA molecules with a length of approximately 22 nucleotides that regulate cellular processes by inhibiting the translation of messenger RNAs. 44 MiRNAs have become a research hotspot on the neurotoxicity of anesthetics in recent years.…”
Section: Noncoding Rnamentioning
confidence: 99%
“…41 microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been found to be involved in the neurotoxicity process of propofol. 42,43…”
Section: The Mechanism Of Propofol On Brain Damage During Developmentmentioning
confidence: 99%
“…The genetic background of higher expression of LRCF can be used as a marker to identify high-risk patients with OLG damage caused by propofol . In addition, it is found that miR-665, miR-9-5p/CXC chemokine receptor 4 (CXCR4) axis, miR-455-3p/EPH receptor A4 (EphA4) axis, miR-363-3p/CREB axis, miR-215/large tumor suppressor homologue 2 (LATS2) axis, miR-34a/mitogen-activated protein kinase kinase (MEK)/ERK signaling pathway, miR-206/p53 upregulated modulator of apoptosis (PUMA) axis, miR-17-5p/Bcl-2-like protein 11 (BCL2L11) axis, and signal transducer and activator of transcription 3 (STAT3)/miR-21/Sprouty 2/Akt signaling pathway are all involved in propofol-induced neuronal apoptosis. ,,, …”
Section: Mechanisms Of Propofol-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…At present, great progress has been made in the treatment of neurotoxicity of general anesthetics by targeting miRNAs. Recent studies have shown that miR-17-5P can alleviate the neurotoxicity induced by propofol and isoflurane exposure ( 34 , 35 ), which may serve as a potential drug direction for future research and development of general anesthetic neurotoxicity. Similarly, Chen et al found that miR-384-3p can alleviate sevoflurane-induced apoptosis and morphological changes of hippocampal neurons, and also improve cognitive impairment, such as the sevoflurane-induced decline in learning and memory ability ( 36 ), which is of great help in relieving and treating cognitive impairment caused by general anesthesia and is a potential new therapeutic strategy.…”
Section: Non-coding Rnamentioning
confidence: 99%